Organic carbon stock changes and crop yield in a tropical sandy soil under rainfed grains-cotton farming systems in Bahia, Brazil - Alexandre Cunha de Barcellos Ferreira; Julio Cesar Bogiani; Valdinei Sofiatti; Ana Luiza Dias Coelho Borin; Fabiano José Perina; Gilvan Barbosa Ferreira; Mellissa Ananias Soler da Silva; Pedro Luiz Oliveira de Almeida Machado (Pesquisa Agropecuária Tropical, 2022)
Most studies about soil organic carbon stock changes in the Cerrado (Brazilian Savanna) biome are either related to field data collected in clayey Ferralsols or different land uses, as if they were in equilibrium. This study aimed to evaluate the effect of tillage systems and crop sequences on the soil organic carbon stock and crop yield, in a sandy Ferralsol from Bahia, Brazil. The experimental design was randomized blocks, with four replicates. Soil samples were collected after five years of cotton, soybean and maize monocropping under heavy disk harrow and leveling harrow (conventional tillage), and of crop rotation of cotton, soybean and maize with green manure or cover crop (no-tillage). Additional samples were collected from a non-cultivated site (Neotropical Savanna, Cerrado sensustricto). Soil conservation practices such as no-tillage and crop rotation with cover crop and green manure favored the soil organic carbon stock at the 0-40 cm layer, with the highest values reaching 36.03 Mg ha-1. The accrued soil carbon stock under conventional tillage and monoculture of cotton, maize and soybean was lower than under no-tillage, which ranged from 30.9 to 54.9 %, with the soil organic carbon stock increasing at the annual rate of 2.36 Mg ha-1 during five years. The no-tillage, with the soybean-maize-cotton rotation, in combination with cover crop and green manure, increased the cotton and soybean yields, with a simultaneous organic carbon accumulation in the sandy soil.